2007
DOI: 10.1093/schbul/sbm105
|View full text |Cite
|
Sign up to set email alerts
|

Questioning an Axiom: Better Prognosis for Schizophrenia in the Developing World?

Abstract: Introduction: That schizophrenia has a better course and outcome in developing countries has become an axiom in international psychiatry. This is based primarily on a series of cross-national studies by the World Health Organization (WHO). However, increasing evidence from other research indicates a far more complex picture. Methods: Literature review and tabulation of data from 23 longitudinal studies of schizophrenia outcomes in 11 low- and middle-income countries. Results: We reviewed the evidence about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(184 citation statements)
references
References 76 publications
(124 reference statements)
7
173
2
2
Order By: Relevance
“…Cohen and colleagues addressed this obvious problem in a review of 23 longitudinal studies of schizophrenia from 11 countries defined as low-and middleincome by the World Bank. 7 These countries included 3 in Africa (Nigeria, Ethiopia and South Africa), 2 in South America (Brazil and Colombia), 2 in the Caribbean (Jamaica and Trinidad), 3 in Asia (India, China and Indonesia) and 1 in Eastern Europe (Bulgaria.) To provide a basis for comparison, these authors included developing world sites from both the DOSMeD and the ISoS.…”
Section: Non-who Data On Outcomementioning
confidence: 99%
See 3 more Smart Citations
“…Cohen and colleagues addressed this obvious problem in a review of 23 longitudinal studies of schizophrenia from 11 countries defined as low-and middleincome by the World Bank. 7 These countries included 3 in Africa (Nigeria, Ethiopia and South Africa), 2 in South America (Brazil and Colombia), 2 in the Caribbean (Jamaica and Trinidad), 3 in Asia (India, China and Indonesia) and 1 in Eastern Europe (Bulgaria.) To provide a basis for comparison, these authors included developing world sites from both the DOSMeD and the ISoS.…”
Section: Non-who Data On Outcomementioning
confidence: 99%
“…Studies from China, Ethiopia, India (Chennai) and Indonesia reported high percentages of subjects who had never received biomedical treatment (with long duration of untreated psychosis) and this was associated with poor outcome. Cohen and colleagues 7 argue that this evidence suggest that good outcome cannot be assumed for schizophrenia in low-and middle-income (LMI) countries -a belief popularized by the WHO studies. These authors also address the issue of mortality and show markedly higher mortality rates in people with schizophrenia in LMI countries compared with the general population.…”
Section: Non-who Data On Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…A more favourable outcome was found in patients from developing countries, once placed in a social context both more heterogeneous and less competitive, they would be less stigmatized for their illness. However, this hypothesis has previously been challenged 27 and a growing body of evidence suggests that this axiom should be re-examined 27 . Other authors have emphasized the differential characteristics of cultures: they suggest that in Latin cultures the society is more protective and supporting than in Anglo-American cultures and thus less stigmatizing, which may also improve the course of schizophrenia 28,29 .…”
Section: Discussionmentioning
confidence: 99%